Detection of COVID-19 Cases in the Hospital of Universitas Brawijaya Malang - Nuning Winaris; Andre William Tulle; Soeyati Poejiani; Sri Andarini; Wening Prastowo; Agustina Tri Endharti; Dwi Yuni Nur Hidayati (Konsorsium Ilmu Biomedik Indonesia (KIBI), 2022)
The global pandemic of COVID-19 was caused by a novel coronavirus identified as SARS-CoV-2. The outbreak started in Wuhan, China and spread rapidly all over the world. Escalation of daily test capacity can accelerate the new suspect of COVID-19 cases finding and rapidly trace the close contacts of confirmed cases. In this study, we reported the total number of confirmed cases based on the number of samples tested in the diagnostic laboratory of the Hospital of Universitas Brawijaya Malang. The data for this study were collected from the result of the RT-qPCR test, which was used as the gold standard to identify active cases of COVID-19. The data collection was started from May 2020 until April 2021. Based on our findings, it appeared that the peak of the first wave of COVID-19 happened between December 2020 and January 2021. Keywords: COVID-19; RT-qPCR; ‎‎‎‎‎‎‎‎‎‎‎‎SARS-CoV-2